2022
DOI: 10.3389/fnut.2022.1048789
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of nutritional and functional properties of different sorghum genotypes for ensuring nutritional security in dryland agro-ecosystem

Abstract: The cultivation of unique sorghum (resistant to abiotic stresses and re-recognized as healthy food) has attracted interest as an environmentally friendly minor cereal and may be a solution to food and nutritional security. However, information about how the use of selected sorghum grains affects nutritive values and its functional properties from sorghum flours is still lacking. To address this question, we selected six sorghum varieties (i.e., JinZa 34, LiaoZa 19, JinNuo 3, JiZa 127, JiNiang 2, and JiaXian) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
4
1
Order By: Relevance
“…Similarly, total dietary fiber and total crude fiber contents were in the ranges of 6.72–16.27 and 0.71–2.62%, with means of 10.51 and 1.51%, respectively. Compared to our study, Htet et al ( 45 ) found comparable fat (2.89–5.14%) and crude fiber (1.58–2.49%) contents in six sorghum varieties grown in China. Protein and lipid levels of 9.57–11.13 and 3.60–5.43%, respectively, have also been reported in five Brazilian sorghum hybrids ( 16 ).…”
Section: Resultscontrasting
confidence: 67%
“…Similarly, total dietary fiber and total crude fiber contents were in the ranges of 6.72–16.27 and 0.71–2.62%, with means of 10.51 and 1.51%, respectively. Compared to our study, Htet et al ( 45 ) found comparable fat (2.89–5.14%) and crude fiber (1.58–2.49%) contents in six sorghum varieties grown in China. Protein and lipid levels of 9.57–11.13 and 3.60–5.43%, respectively, have also been reported in five Brazilian sorghum hybrids ( 16 ).…”
Section: Resultscontrasting
confidence: 67%
“…The value obtained in the present study makes it still safe for onset hypertensive patients if consumed. In general, the mineral composition of sorghum-soybean composite flour was higher than those reported for different varieties of whole sorghum grains [10]. This trend is definitely envisaged due to improvement upon fortification of sorghum by soybean in this study.…”
Section: Nd = Not Detectedsupporting
confidence: 44%
“…This factor makes it a substitute for wheat in bakery and brewing industries as well as in the preparation of local wine called "Burukutu" in Yoruba tribe of Nigeria; pap and additive for local milk drink called "Fura de nunu" in Hausa tribe of Nigeria. "It is a multipurpose minor cereal crop primarily used as food, feed, forage, most importantly as raw material for brewing liquor [9,10] and valueadded food products" [11]. "It is also widely grown on dry-land agricultural systems in arid and semiarid specific zones of northern and northeastern parts of China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male sterile lines in sorghum grains are essential for the generation of hybrids and the enhancement of grains. Researchers exploit heterosis to enhance production and crop characteristics [16,17], exploring male sterility induction techniques in sorghum and focusing on several ways to improve yield and quality in sorghum breeding programs [18,19]. Developers use controlled hybridizations, male sterility lines, crop growth patterns, and pollination tendencies in sorghum breeding to optimize nutritional qualities [20].…”
Section: Introductionmentioning
confidence: 99%